2011
DOI: 10.1111/j.1365-2672.2011.04944.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of three virulence genes alt, ahp and aerA in Aeromonas hydrophila and their relationship with actual virulence to zebrafish

Abstract: Aims:  To evaluate the frequency of the aerolysin (aerA), cytotoxic enterotoxin (alt) and serine protease (ahp) genes in Aeromonas hydrophila isolates from different sources, and to determine the relationship between the presence of these genes and virulence of A. hydrophila in zebrafish. Methods and Results:  Aeromonas hydrophila isolates from clinical cases (n = 40), from healthy fish (n = 22) and from water environment (n = 21) were analysed with respect to the prevalence of aerA, alt and ahp genes by PCR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
79
1
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(101 citation statements)
references
References 33 publications
9
79
1
8
Order By: Relevance
“…et al 2005). Only 12.28% (14/114) of isolates in this study showed no virulence factor, which corroborates with the data in the literature (Li et al 2011). This fact conϐirms the high pathogenicity potential of A. hydrophila coming from ϐish, which suggests their high capability of causing disease in ϐish, especially because they were mostly isolated from diseased animals.…”
Section: Aeromonas Hydrophila Inoculation With Different Frequencies supporting
confidence: 91%
See 1 more Smart Citation
“…et al 2005). Only 12.28% (14/114) of isolates in this study showed no virulence factor, which corroborates with the data in the literature (Li et al 2011). This fact conϐirms the high pathogenicity potential of A. hydrophila coming from ϐish, which suggests their high capability of causing disease in ϐish, especially because they were mostly isolated from diseased animals.…”
Section: Aeromonas Hydrophila Inoculation With Different Frequencies supporting
confidence: 91%
“…may be associated with several factors, and isolates from human patients usually do not have a signiϐicant genetic relationship with the pathogens of aquatic organisms. This fact may be associated with the results reported in this study, especially considering that other virulence factors, in addition to those studied in this paper, have also been described as virulence markers in A. hydrophila (Li et al 2011).…”
Section: Aeromonas Hydrophila Inoculation With Different Frequencies supporting
confidence: 76%
“…Several recent studies reported the involved virulence factors in fish infections (11,17,36). The primary challenge in establishing an unequivocal link between the Aeromonas genus and pathogenesis is the extremely complicated taxonomy.…”
mentioning
confidence: 99%
“…Thus, Li et al (2011) evaluated the relationship between the presence of the aerolysin (aerA), cytotoxic enterotoxin (alt) and serine protease (ahp) genes, and virulence of A. hydrophila isolates in zebra fish. The authors conclude that the aerA+alt+ahp+ isolates were more virulent to zebra fish than other single or two-virulence-factor combination strains.…”
Section: Haemolysins and Phospholipasesmentioning
confidence: 99%